Tissue-specific and species-specific monoclonal antibodies to avian red cell nuclear proteins. - Kane, C M (1982)
In order to identify potential red cell-specific regulatory proteins and to define additional red cell-specific markers, we have isolated a series of hybridomas that produce monoclonal antibodies that react with nuclear preparations from avian red blood cells. Several antibodies have been well characterized for their tissue- and species-specific reactions by using solid-phase and protein-transfer radioimmunoassays as well as immunofluorescence. These antibodies should allow isolation and characterization of individual nuclear proteins that are tissue and species specific and may prove useful for the study of gene expression in the erythropoietic system. The majority of the well-characterized antibodies appear to have tissue-specific properties. However, three antibodies react with all tested chicken tissues; one of these reacts with multiple peptides in a pattern that varies qualitatively and quantitatively between the tissues. This may reflect a common protein domain or modification that is used in several different tissues for similar functions but is nevertheless present in an overall protein framework that is tissue specific. Because the major fraction of the hybridomas initially produced is tissue specific, we presume that the immune system selects for tissue-specific determinants. This property of the immune system may prove to be a useful general feature of this type of analysis.